2016
DOI: 10.1007/s11682-015-9501-6
|View full text |Cite
|
Sign up to set email alerts
|

Impaired topological architecture of brain structural networks in idiopathic Parkinson’s disease: a DTI study

Abstract: Parkinson's disease (PD) is considered as a neurodegenerative disorder of the brain central nervous system. But, to date, few studies adopted the network model to reveal topological changes in brain structural networks in PD patients. Additionally, although the concept of rich club organization has been widely used to study brain networks in various brain disorders, there is no study to report the changed rich club organization of brain networks in PD patients. Thus, we collected diffusion tensor imaging (DTI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 85 publications
6
42
1
Order By: Relevance
“… 9 Predominantly neurodegenerative diseases such as Parkinson disease seem to be associated with a pronounced loss of peripheral and feeder connections. 11 , 26 Within this context, our findings indicate that diffuse perturbations of brain connectivity in PPMS result in a pronounced loss of connectivity within the rich club, and that the overall pattern of connectivity loss differs from primarily neurodegenerative diseases. However, this cross-sectional study does not allow to distinguish between the impact of inflammatory and neurodegenerative mechanisms on the assessed connectivity loss.…”
Section: Discussionmentioning
confidence: 71%
“… 9 Predominantly neurodegenerative diseases such as Parkinson disease seem to be associated with a pronounced loss of peripheral and feeder connections. 11 , 26 Within this context, our findings indicate that diffuse perturbations of brain connectivity in PPMS result in a pronounced loss of connectivity within the rich club, and that the overall pattern of connectivity loss differs from primarily neurodegenerative diseases. However, this cross-sectional study does not allow to distinguish between the impact of inflammatory and neurodegenerative mechanisms on the assessed connectivity loss.…”
Section: Discussionmentioning
confidence: 71%
“…A similar study by Batista et al suggested that cognitive and motor decline in early stages of PD is associated with microstructural changes of white‐matter that extended to the frontal, parietal and temporal regions [Batista et al, ]. These findings were confirmed by a recent study conducted by Li et al in which a widespread pattern of decreased efficiency was found in PD patients relative to healthy controls [Li et al, ].…”
Section: Introductionmentioning
confidence: 64%
“…In very recent years few studies have also investigated the presence of altered structural connectivity patterns in PD patients using DTI‐based graph analyses [Aarabi et al, ; Batista et al, ; Li et al, ; Pereira et al, ]. For example, Aarabi and colleagues combined DTI and network‐based statistics (NBS) to reveal reduced connectivity in PD in networks comprising motor and non‐motor regions such as cingulum, temporal and frontal regions, parahippocampus, olfactory lobe, and occipital lobe [Aarabi et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) is a powerful tool to investigate microstructural alterations to the human brain in vivo. In PD, this technique has been combined with voxel‐ or region‐of‐interest (ROI)‐wise (Atkinson‐Clement, Pinto, Eusebio, & Coulon, ; Schwarz et al, ), and graph‐theoretical analyses (Aarabi et al, ; Li et al, ; Nigro et al, ; Pereira et al, ). Tract‐based spatial statistics (TBSS) is a voxel‐wise method, specifically developed to minimize the methodological pitfalls caused by misalignment and misregistration in conventional voxel‐based analyses (Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%